Equality of Opportunity and Optimal Cash and In-Kind Policies - Leonardo Gasparini; Santiago Pinto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This paper examines the argument for public provision of certain private goods, like education and health, based on equality of opportunity by studying the utility possibility frontier of a society in which there is a concern for the distribution of these goods. A given quality of education or health services can be consumed for free in the public sector, but people can opt-out and purchase their desired quality levels in the private sector. Some of the conclusions are: (i) a pure cash transfer is optimal when the utility redistribution is either “sufficiently” small or large; (ii) if and only if both the equality-of-opportunity concern and the utility redistribution are large enough, can an in-kind program which attracts the whole population be justified; (iii) even when everybody chooses the in-kind program, it may be optimal to perform some additional utility redistribution by increasing the size of such program.
Keywords: D3; H4; I2; 330; equality of opportunity; redistribution; education; in-kind